PENGARUH CELEBRITY WORSHIP TERHADAP PERILAKU AGRESI VERBAL DALAM BERMEDIA SOSIAL PADA PENGGEMAR KOREAN POP (K-POP) BOYBAND NEO CULTURE TECHNOLOGY (NCT) DI INDONESIA - Pangkerego, Marcela E.; Naharia, Melkian; Mandang, Jofie H. (PSIKOPEDIA, 2025)
Abstract : This study aims to determine the effect of Celebrity Worship on Verbal Aggression in Social Media on Fans of Korean Pop (K-Pop) Boyband Neo Culture Technology (NCT) in Indonesia. The type of research used is quantitative research. The sample used amounted to 96 people. The results showed Celebrity Worship had a significant and linear effect on Verbal Aggression. This can be proven based on the results of the T test analysis which shows a significance value of 0.000 (p <0.05) and the simple linear regression results show a coefficient number of 0.811 with a positive value.